PEMODELAN SISTEM PENDUKUNG KEPUTUSAN KELOMPOK UNTUK DIAGNOSA PENYAKIT PNEUMONIA DENGAN FUZZY LINGUISTIC QUANTIFIER DAN AHP - Syaukani, Muhammad; Hartati, Sri (Jurnal Ilmu Komputer; Vol. 5, No. 1 April 2012, 2012)
Group Decision Support System (GDSS) is a computer based systems that support groups of people involved in a common goal. Pneumonia is an infection of the alveoli and the end of bronkiol and that most diseases result in death for each year, lack of medical personnel at health centers compared with the population resulted in frequent delays service to the patient's pneumonia. This study focused on the development of group decision support system for diagnosis pneumonia in adult patients. The system is designed to help medical personnel in diagnosis pneumonia patients and reduce the level of delays in treatment for pneumonia patients and minimize the error giving antibiotics to pneumonia patients.Group Decision Support System was developed using a web based PHP programming language while to process the knowledge database using MySQL database, to give a decision table which is an association between symptoms and disorders, as well as giving preference value of the three experts, namely the pulmonary experts, internists experts and pharmacists use Triangular Fuzzy. In the aggregation stage of preferences used Fuzzy Linguistic quantifiers and phase perangkingan using AHP. The system was tested by entering the symptoms of pneumonia without the involvement of an expert. The results showed that the system could support to diagnosis pneumonia.
Keywords: GDSS, Fuzzy Linguistic Quantifier, AHP, Pneumonia